Innovations in government research, recognition, and replication - Borins, Sandford F. 1949-. (Washington, D.C. Brookings Institution Press, 2008)
"Answers questions on the future of government innovation and its effect on citizens and democratic governance by presenting a comprehensive approach to advancing the practice and study of innovation in government. Discusses new research on innovation, explores the impact of programs that recognize innovation, and considers challenges to replicating innovations"--Provided by publisher.
Twenty years of highlighting excellence in government / Jonathan Walters -- The "Kennedy School school" of research on innovation in government / Steven Kelman -- Citizen participation in government innovations / Archon Fung -- Subnational government innovation in a comparative perspective : Brazil / Marta Ferreira Santos Farah and Peter Spink -- The unaccustomed inventiveness of the Labor Department / John D. Donahue -- Developmental processes : a conceptual exploration / Eugene Bardach -- The adoption of innovation : the challenge of learning to adapt tacit knowledge / Robert D. Behn -- Does innovation lead to improvement in public services? : lessons from the Beacon Scheme in the United Kingdom / Jean Hartley -- Innovations in government : serving citizens and strengthening democracy / Gowher Rizvi -- Research on innovations in government : what next? / Sandford Borins.
"Ash Institute for Democratic Governance and Innovation, John F. Kennedy School of Government, Harvard University."
Keywords: Political planning; Organizational change